2013
DOI: 10.1021/ie401364d
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Lignin Structure during Alkaline Delignification of Eucalyptus Wood by Kraft, Soda-AQ, and Soda-O2Cooking

Abstract: The modification of the lignin structure of an eucalyptus feedstock during alkaline delignification by kraft, soda-AQ, and soda-O 2 cooking processes has been investigated by different analytical techniques (size exclusion chromatography (SEC), pyrolysis gas chromatography−mass spectroscopy (Py-GC/MS), 1 H− 13 C two-dimensional nuclear magnetic resonance (2D-NMR), and 31 P NMR). The characteristics of the lignins were compared at different pulp kappa levels, and with the native lignin isolated from the wood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 42 publications
6
72
0
1
Order By: Relevance
“…(Yuan et al 2009) The FTIR spectra of the four alkali lignins are shown in Fig. 1, and the notable peak assignments can be referenced from previous studies (Tahmli et al 1999;Sun et al 2005;Ounas et al 2011;Lv et al 2013;Prinsen et al 2013). The absorbance of peak 1 located at (3420 cm -1 ) was due to the O-H stretching vibration, in which the absorption area of the four lignins was relatively large, showing that the four lignins were all abundant in the O-H group.…”
Section: Chemical Structure Of Alkali Ligninsmentioning
confidence: 87%
“…(Yuan et al 2009) The FTIR spectra of the four alkali lignins are shown in Fig. 1, and the notable peak assignments can be referenced from previous studies (Tahmli et al 1999;Sun et al 2005;Ounas et al 2011;Lv et al 2013;Prinsen et al 2013). The absorbance of peak 1 located at (3420 cm -1 ) was due to the O-H stretching vibration, in which the absorption area of the four lignins was relatively large, showing that the four lignins were all abundant in the O-H group.…”
Section: Chemical Structure Of Alkali Ligninsmentioning
confidence: 87%
“…Of these methods, chemical pulping accounts for 70% of the total pulp production, with the sulfate process (i.e., kraft process) being the most utilized chemical pulping method worldwide. During chemical pulping, the web-like structure of lignin is degraded, and lignin is dissolved through chemical reactions at elevated temperatures (Prinsen et al 2013). The liberated fibers can then be separated from the cooking liquor, washed, and bleached.…”
Section: Alkaline Pulping Of Pretreated Woodmentioning
confidence: 99%
“…However, the sulfur compounds formed during kraft process can cause odor problems already at extremely low concentrations Gomes 2002, 2003). Alternative pulping methods mainly comprise sulfur-free alkaline processes, usually in the presence of some catalysts, such as soda cooking combined with the AQ catalyst (Biermann 1996;Feng et al 2002a,b;Ban et al 2009;Prinsen et al 2013;Ikeda and Magara 2015). Without the catalyst, sulfur-free alkaline cooking has some disadvantages.…”
Section: Soda-anthraquinone Pulpingmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena generated new free phenolic hydroxyl groups, as observed in the isolated lignin from pulp, when compared with lignins from wood (Table 4). Prinsen et al (2013), indicated that a high content of phenolic hydroxyl groups in dioxane lignin in pulps is the result of high levels of β-O-4 bonds in wood lignin. This tendency is also observed in the Eucalyptus globulus genotypes of the present study as shown in figure 5 (r=0,92; p=0,008).…”
Section: P Nmrmentioning
confidence: 99%